Phenomenological Prediction of the Band Diagram of Organic–Organic and Inorganic–Organic Heterointerfaces. Issue 2 (20th May 2020) - Muench, Maybritt; Mankel, Eric; Mayer, Thomas; Jaegermann, Wolfram
Abstract: Herein, a phenomenological rule is presented for the estimation of electronic contact properties of organic–organic and inorganic–organic hetero interfaces, which is deduced from a large number of experimentally studied heterojunctions. The data for the present study are summarized from in situ step‐by‐step interface experiments using photoelectron spectroscopy. Organic and inorganic (oxide) materials are investigated which are used for the manufacturing of organic based optoelectronic devices in the InnovationLab Heidelberg. It is shown that the measured values of the interface dipole as well as of the band bending linearly depend on the work function difference between substrate and adsorbate. The data suggest that the investigated materials as technologically applied films contain a prototypical concentration of electron states at the interface and in the bulk, the charge of which is adjusted to reach thermodynamic equilibrium at a contact. As a consequence, a generally applicable empirical formula to predict the energetic band alignment due to dipole formation and the contact potential distribution due to band bending can be deduced, which is given by just the work function differences between the pristine layers. This result suggests that band bending as well as interface dipole formation are both attained by redistribution of electronic charge via integer charge transfer processes. Abstract : A phenomenological rule determines the electronic contact properties of organic–organic and inorganic–organic hetero interfaces as deduced from experimentally studied heterojunctions. The measured value of the interface dipole and band bending linearly depends on the work function difference of the pristine materials. This result suggests that contact formation is governed mostly by the redistribution of electronic charge via integer charge transfer processes.